Tindakan Tembak Mati Terhadap Terduga Teroris Berdasarkan Perspektif Proses Hukum Yang Adil - July Wiarti (Lex Renaissance, 2019)
The process of law enforcement for the criminal acts of terrorism that should have been carried out from investigation to execution is often cut down to violations by the authorities, namely the Special Detachment (Densus) 88, such as arbitrary arrest, wrongful arrest and suspected death-shooting of terrorists without proper procedures. Based on these, the research will discuss two issues, first, how is the process of determining someone declared a terrorist suspect? Second, how is the implementation of the act of shooting to death suspected terrorists by Densus 88 in the perspective of due process of law? This study uses a normative juridical method which the data collection method is done through literature study and analyzed in descriptive-qualitative manner. The conclusions of this research are, first, the process of determining a person is declared a suspected terrorist is that a person suspected of having committed or attempted to commit, or participating in and/or facilitating a criminal act of terrorism is based on sufficient preliminary evidence, which is required at least 2 (two) valid evidence. Second, the execution of the act of death-shooting against the suspected terrorists by Densus 88 in the perspective of due process of law is when the authorities use firearms at the last step and may only be used for urgent conditions and preceded by a warning.